India and the politics of climate change: policy paradigms and the local city state - Deshpande, Tanvi (2022)
Cities from the Global South like India, housing high concentration of population, are highly vulnerable to the impacts of climate change, especially water scarcity. Since water insecurity threatens urban resilience, cities need to cope with (adaptation) and reduce the impacts (mitigation) of climate change. The main research question of this study is: why do comparable Indian cities have different outcomes in improving water security and pursuing climate action? In doing so, the study contributes to comparative politics and climate governance literature by providing evidence from the Global South. Two medium sized and non-metropolitan cities- Rajkot in the state of Gujarat and Aurangabad in the state of Maharashtra- were identified using the Mill’s Method of Difference. Despite fairly comparable characteristics and governance challenges, the two cities are pursuing different policy paradigms overtime- a climate friendly with improved water security and climate action (Rajkot) versus a climate regressive one with severe water insecurities and no climate action (Aurangabad). Rajkot was able to overcome governance challenges such as clientelistic and rent-seeking practices to make policy adjustments serving all citizens. Following a state centric approach, the study argues that, improved state capacity at the local level to pursue its stated objectives, in this case provide regular water supply, is attributed to ideational factors, that is values and beliefs held by the city government. Ideas within the city government evolve overtime due to the process of puzzling and powering within the state. The study compared the administrative tradition and political commitments of the city governments to understand the process of puzzling and powering. Empirical evidence for the cities was collected through in-depth field engagements in India. The study relies mainly on primary data (government and NGO reports, meeting minutes, municipal resolutions & orders and newspaper articles and interviews). Using a historical institutional approach, the study has traced and compared water adaptation and mitigation policies introduced by the two cities across a common timeframe (1990-2020).